(Cationic + nonionic) mixed surfactant aggregates for solubilisation of curcumin. (February 2016) - Kumar, Arun; Kaur, Gurpreet; Kansal, S.K.; Chaudhary, G.R.; Mehta, S.K.
Graphical abstract: Highlights: Critical micelle concentration of mixed surfactant has been measured. Aqueous solubility and alkaline stability of curcumin has been significantly improved. Location of curcumin within micelles has been evaluated. Scavenging activity of curcumin has been improved. Non-intercalative binding with ct-DNA has been observed. Abstract: Curcumin is a potential drug for variety of diseases. Major limitations of curcumin are low water solubility, rapid hydrolytic degradation in alkaline medium and poor bioavailability. To overcome these limitations, highly potential mixed micellar system has been prepared. In order to reduce inter ionic repulsion and precipitation of surfactants, (cationic + non-ionic) mixed system have been chosen that directly influence its applicability. Hydrophobic chain of non-ionic surfactant significantly influences the cmc of mixed surfactant system as indicated by fluorescence and conductivity data. UV–visible spectroscopy analyses show that solubility, stability and antioxidant property of the curcumin is remarkably improved depending on cmc and aggregation number ( N agg ) of mixed surfactants, where N agg plays crucial role. Generally, curcumin undergoes complete degradation in slight basic medium, but stability has been maintained up to 8 h at pH-13 using formulated mixed micelles (only (20 to 25)% degraded). Location of curcumin which is monitored using emission spectroscopy, fluorescence quenching and 1 H NMR spectroscopy techniques play the most important role. Observed results show that the major population of curcumin is located at the polar region and some are in hydrophobic region of the mixed micelles. To ensure the effect of mixed surfactants and curcumin loaded mixed surfactants on DNA, the interaction parameter indicates non-interclative interactions.